Pengaruh Variasi Ukuran Partikel pada Pembuatan Bio-Briket dari Pelepah dan Tandan Buah Kosong Kelapa Sawit - Syukri, Muhammad; Maisarah; Rangkuti, Ika Ucha Pradifta; Rahimah; Tama Harahap, Khaidir Ali; Nurhidayat, Taufik (Talenta Publisher (Universitas Sumatera Utara), 2024)
Palm oil empty fruit bunches (EFB) and fronds are solid waste originating from palm oil processing which can be used as the main raw material for making briquettes. This is supported by its contents, namely lignin, hemicellulose and cellulose. The smaller the particle size, the greater the compressive strength of the briquette, but the burning rate will be slower because the cavity/pores of the briquette are smaller. This research aims to determine the effect of particle (mesh) size on the characteristics of briquettes which include water content, ash content, density, compressive strength and burning rate as well as to determine the best composition of a mixture of empty oil palm fruit bunches and fronds. The results of this research show that the best particle size is 70 mesh briquettes with a raw material composition of 46% EFB and 46% fronds (1:1) with 8% tapioca flour adhesive. Biobriquettes with small particle sizes have lower calorific value. The results of this research indicate that the manufacture of briquettes is in accordance with the Standard Characteristics of SNI No. 1/6235/2000.